Bhakta Narasiṃhanuṃ adhyātmadarśana - Bhāṇadeva (Gūrjara Prakaśana, 2021)
Spiritualism and philosophy in the works of Narasiṃha Mehetā, 1414-1481, Gujarati poet
Keywords: Narasiṃha Mahetā; Lyrik; Spiritualität